OVERVIEW OF DIABETIC NEUROPATHY - Ali Nasser Mansour Shammakhi; Tareq Ahmed Ali Khormi; Ghason Ali A Torki; Mohammed Ali Hussein Alhazmi; Ibraheem Sindi Shetifi; Majed Hameed Alharbi; Abualgassam Nasseer Mohmmed Zwogan; Khaled Mossa Mohsen Mashi; Nahla Shaker Saati; Saleh Mohammed Shami; Feher Mohammed Alturkistani; Ahmed Sameer Munshi; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Diabetic neuropathy, impacting both type 1 and type 2 diabetes patients, stems from prolonged high blood sugar damaging nerves, leading to diverse symptoms like discomfort and numbness. Various physiological mechanisms, including hyperglycemia and prediabetes, contribute to its development, while psychological factors also impact patients' quality of life. Diagnosis involves comprehensive evaluations, including nerve conduction studies and skin biopsy. Prevention strategies focus on strict glycemic control, lifestyle adjustments, and early intervention, with exercise, neurostimulation devices, and nutraceuticals showing promise in managing neuropathic pain. Pharmaceutical treatments alleviate symptoms but may cause adverse effects. Herbal remedies, like flavonoids, offer alternative therapeutic options with potential benefits in reducing inflammation and oxidative stress, presenting a multifaceted strategy for diabetic neuropathy management. Aim: to understand diabetic neuropathy, covering its causes, symptoms, pathophysiology, diagnosis, control and prevention, and treatment options to improve treatment outcomes. Methods: a comprehensive review of Diabetic neuropathy and therapy. The PUBMED and Google Scholar search engines were the main databases used for the search process, with articles collected from 2007 to 2022. Conclusion: Diabetic neuropathy, prevalent in both type 1 and type 2 diabetes, results from prolonged high blood glucose levels damaging nerves. Symptoms vary from discomfort to numbness and autonomic issues. Prediabetes is also linked to neuropathy, stressing early detection. Pathophysiologically, factors like glycemic dysregulation and oxidative stress contribute to nerve damage. Diagnosis involves nerve conduction studies and clinical evaluation, though early detection challenges persist. Prevention emphasizes glycemic control, lifestyle adjustments, and emerging therapies like neurostimulation. Medications offer symptom relief, while herbal remedies and flavonoids show promise. Managing diabetic neuropathy requires a multifaceted approach integrating traditional and emerging treatments for improved patient outcomes and quality of life.